KONSISTENSI METODE SIMPLEKS DALAM MENENTUKAN NILAI OPTIMUM - Rina Lusiana Rumahorbo; Abil . Mansyur (KARISMATIKA: Kumpulan Artikel Ilmiah, Informatika, Statistik, Matematika dan Aplikasi, 2017)
ABSTRACTThis study,entitled “Consistency of Simplex Method to Determine the Optimum value”. This study aims to show how Consistency Simplex Method in Determining the Optimum Value. The data used in this research is secondary data, the data is data that has optimum completion. To obtain solutions that provide optimum value in this study first conducted by registering all possible solutions and then look for the most optimum value of all possible solutions. Furthermore, the linear programming problem will be solved using the simplex method. The study begins from assessing the optimal solution concepts in general, the next step Simplex method described step by step. Every step of the Simplex method were analyzed through observation to check whether the results meet the criteria Optimum. From the first step in formulating the problem of linear programming in the form of ready simplex, then enter an equation into a table simplex early, determine the key column, row lock and key numbers to the stage of checking solutions dieroleh table simplex, simplex method shows that each stage that passed by consistent to a point. The destination point in this case is the point that gives the optimum value. In this study, there were three cases of maximization and minimization three cases were solved by the simplex method, and from the obtained solution simplex method consistently deliver value really optimum for each case.